HUBUNGAN DUKUNGAN KELUARGA DAN TEMAN SEBAYA TERHADAP KECEMASAN DALAM PROSES PEMBELAJARAN SAAT PANDEMI COVID 19 PADA SISWA DI SMPN 5 DEPOK - Chaerani (2021)
The COVID-19 pandemic has affected the education sector with the implementation of distance learning so that it can have a psychological impact on teenagers. In its implementation, it takes the support of family and peers so that teenagers feel more cared for and loved. This study aims to determine the relationship between family and peer support for anxiety in the learning process during the COVID-19 pandemic in students at SMPN 5 Depok. The research design was cross sectional with a stratified random sampling technique of 242 students. Data analysis using chi square test. The results of the analysis between family support and anxiety obtained p value = 0.002 (<0.05) meaning that there is a relationship between family support and anxiety in learning. While the results of the analysis on peer support with anxiety obtained p value = 0.025 (<0.05) meaning that there is a relationship between peer support and anxiety in the learning process. The implication of the research is to know the relationship between family and peer support for learning anxiety in adolescents so that the psychological impact during the COVID-19 pandemic can be minimized.